Natural Killer Cells and Host Defense Against Human Rhinoviruses Is Partially Dependent on Type I IFN Signaling - van der Heide, Saskia L.; Xi, Yang; Upham, John W. (Frontiers in Cellular and Infection Microbiology, 2020)
Rhinovirus (RV), the causative agent of the common cold, causes only mild upper respiratory tract infections in healthy individuals, but can cause longer lasting and more severe pulmonary infections in people with chronic lung diseases and in the setting of immune suppression or immune deficiency. RV-infected lung structural cells release type I interferon (IFN-I), initiating the immune response, leading to protection against viruses in conjunction with migratory immune cells. However, IFN-I release is deficient in some people with asthma. Innate immune cells, such as natural killer (NK) cells, are proposed to play major roles in the control of viral infections, and may contribute to exacerbations of chronic lung diseases, such as asthma. In this study, we characterized the NK cell response to RV infection using an in vitro model of infection in healthy individuals, and determined the extent to which IFN-I signaling mediates this response. The results indicate that RV stimulation in vitro induces NK cell activation in healthy donors, leading to degranulation and the release of cytotoxic mediators and cytokines. IFN-I signaling was partly responsible for NK cell activation and functional responses to RV. Overall, our findings suggest the involvement of NK cells in the control of RV infection in healthy individuals. Further understanding of NK cell regulation may deepen our understanding of the mechanisms that contribute to susceptibility to RV infections in asthma and other chronic lung diseases.